Feng Yunhua's academic viewpoint on blood stasis syndrome and nursing practice for promoting blood circulation and resolving blood stasis in optimizing Traditional Chinese Medicine nursing plan for chest obstruction and heart pain (冯运华血瘀证与活血化瘀护理学术观点优化胸痹心痛病中医护理方案的实践) - SONG Libo (宋丽波); JI Cong (纪聪); ZHAO Nan (赵楠); LI Xu (李旭); LI Jing (李静); JING Jing (景静); YANG Lili (杨丽丽); ZHANG Xiaoying (张晓颖); WANG Fengxian (王凤仙) (Journal of International Translational Medicine Limited, 2023)
Objective To explore the clinical practice effect and optimization method of optimizing the Traditional Chinese Medicine (TCM)nursing plan for chest obstruction and heart pain (coronary heart disease) based on Feng Yunhua's academic viewpoint of blood stasis syndrome and nursing for promoting blood circulation and resolving stasis. Methods The clinical data of 793 patients with chest obstruction and heart pain admitted to the hospital from June 2021 to May 2022 were retrospectively analyzed. Totally 390 patients with hospital admission between June 2021 and November 2021 were recruited as the control group, receiving routine nursing plan of promoting blood circulation and resolving blood stasis. Another 403 patients with hospital admission between December 2021 and May 2022 were included as the observation group, received modified nursing plan. Effect of nursing interventions on main symptoms and syndrome integral of blood stasis syndrome were measured, and patient satisfaction and evaluation of nursing program by nurses were investigated. Results The effect of nursing interventions on chest tightness/chest pain and Palpitations/shortness of breath were higher in the observation group than those in the control group(P<0. 01). Better improvement of syndrome integral was reported in patients of observation group compared with that in the control group(P<0. 01). The satisfaction rate in the observation group was higher than that in the control group (P<0. 01). Nurses in the observation group believed that modified nursing plan was more applicable in clinical setting(P<0. 01). Conclusion The implementation of the optimization plan has significant value in improving the nursing effect of patients with major symptoms and blood stasis syndrome scores, and promoting the improvement of TCM nursing satisfaction. Based on Feng Yunhua's academic viewpoints on blood stasis syndrome and nursing for promoting blood circulation and resolving stasis, optimize TCM nursing plan has been carried out to achieve accurate treatment and promote recovery of patients with chest obstruction and heart pain. At the same time, it has improved the ability of nursing staff to provide dialectical care, improved patient satisfaction and treatment compliance, and provided theoretical basis for the optimization of TCM nursing programs for chest obstruction and heart pain. (目的 探讨基于冯运华血瘀证与活血化瘀护理学术观点优化胸痹心痛病(冠心病)中医护理方案(以下简称方案)临床实践效果及优化方法。方法 回顾性分析中国中医科学院西苑医院2021年6月-2022年5月收治的793例胸痹心痛病患者的临床资料, 其中2021年6月-11月收治的患者390例为对照组, 2021年12月-2022年5月收治的患者403例为观察组。评估优化方案实施前后两组患者主要症状护理效果、冠心病血瘀证积分, 对比两组患者满意度和责任护士对中医护理方案实用性的评价。结果 胸闷/胸痛、心悸/气短护理效果比较, 观察组优于对照组, 差异有统计学意义(P<0. 01)。观察组患者血瘀证证候积分改善优于对照组, 差异有统计学意义(P＜0. 01)。观察组患者满意度评价优于对照组, 差异有统计学意义(P<0. 01)。与对照组相比, 观察组责任护士认为中医护理方案实用性更强, 差异有统计学意义(P<0. 01)。结论 优化方案的实施在改善患者主要症状护理效果、血瘀证积分改善有显著价值, 促进了中医护理满意度的提升。基于冯运华血瘀证与活血化瘀护理学术观点优化胸痹心痛病中医护理方案, 使患者能得到精准治疗护理, 促进康复。同时, 提高了护理人员的辨证施护能力, 提高了患者的满意度及治疗的依从性, 为胸痹心痛病中医护理方案的优化提供理论依据。)